2021
DOI: 10.1097/brs.0000000000004006
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Low Back Pain After Posterior Decompression for Lumbar Spinal Stenosis

Abstract: Study Design. A retrospective study.Objective. The aim of this study was to confirm that decompression for lumbar spinal stenosis (LSS) relieves low back pain (LBP) as adequately as it relieves leg pain and to identify predictors for inadequate LBP relief. Summary of Background Data. Although decompression for LSS is generally thought to yield worse results for LBP than for leg pain, some studies have reported similar improvements in pain scores between LBP and leg pain. To treat LBP or take measures to preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Hence, the posterior decompression surgery was suggested for patients with leg predominant symptoms. [ 44 , 45 ] Our meta-analysis demonstrated that the leg pain had no significant difference between IPD treatment and alone decompression surgery at different time-points of follow-up (6, 12 mo and the last follow-up). We considered that patients in both groups received traditional decompression surgery, which effectively alleviated leg pain by nerve root decompression.…”
Section: Discussmentioning
confidence: 86%
“…Hence, the posterior decompression surgery was suggested for patients with leg predominant symptoms. [ 44 , 45 ] Our meta-analysis demonstrated that the leg pain had no significant difference between IPD treatment and alone decompression surgery at different time-points of follow-up (6, 12 mo and the last follow-up). We considered that patients in both groups received traditional decompression surgery, which effectively alleviated leg pain by nerve root decompression.…”
Section: Discussmentioning
confidence: 86%
“…Although our commonly used posterior lumbar decompression surgery can adequately relieve leg symptoms, patients with low back pain often fail to achieve the desired results. 4 The concept of Modic change (MC), reported by Modic in 1988, has been accepted and discussed in the medical community, but its connection to low back pain remains obscure and worth exploring. 5 At present, MC is generally divided into three different types: type I MC (MCI) represents in ammatory edema of the bone marrow, type II (MCII)represents steatosis from red to yellow bone marrow, and type III (MCIII) changes represent the endplate hardening.…”
Section: Introductionmentioning
confidence: 99%
“…Among degenerative changes in the spine, degenerative disc disease (5), facet joint osteoarthritis (6), and lumbar spinal stenosis are the most common anatomical findings (7). As the discs continue their degenerative process, some patients develop intervertebral vacuum phenomenon (IVP), a relatively common finding, especially with advanced degeneration (8).…”
Section: Introductionmentioning
confidence: 99%